Model Pengelolaan Pendidikan Karakter Di Rumah Qur'an Aisyah Radiyallahun'anha - Yanti Nurdiyanti Nurdiyanti; Eko Budi Prasetyo; Muaz ...; Aan Hasanah; Bambang Samsul Arifin (AL-ASASIYYA: Journal Of Basic Education, 2022)
This study aims to examine the development of a character education management model at Rumah Qur'an Aisyah Radiyallahu'anha. The method used is qualitative with a case study approach. Data collection techniques were carried out using interviews and documentation. Data analysis using miles and hubarman model. The results showed that the values of character education at Rumah Qur'an Aisyah Radiallahu'anha focused on 5 values of character education, namely: religious, love of science, social care, nationalism, and entrepreneurial spirit. With the aim of realizing the understanding and practice of Dinul Islam, the growth of people's love for the Qur'an, the development of community behavior that reflects morality, the creation of an intelligent, independent, and mutually helpful society and the formation of a culture of greetings, smiles, greetings, greetings, and kindness. polite (5S) in everyday life. The form of Character Education Management at the Qur'an Aisyah Radiyallahu'anha House consists of Character Education Planning with implementation carried out through a process; care (care), share (share) and trust (trust). This method is effective because everyone is very receptive if there is someone or an institution who cares about him, and from that concern arises sharing.